CD40L controls obesity-associated vascular inflammation, oxidative stress, and endothelial dysfunction in high fat diet-treated and db/db mice. (26th September 2017) - Steven, Sebastian; Dib, Mobin; Hausding, Michael; Kashani, Fatemeh; Oelze, Matthias; Kröller-Schön, Swenja; Hanf, Alina; Daub, Steffen; Roohani, Siyer; Gramlich, Yves; Lutgens, Esther; Schulz, Eberhard; et al.
Abstract: Aims: CD40 ligand (CD40L) signaling controls vascular oxidative stress and related dysfunction in angiotensin-II-induced arterial hypertension by regulating vascular immune cell recruitment and platelet activation. Here we investigated the role of CD40L in experimental hyperlipidemia. Methods and results: Male wild type and CD40L −/− mice (C57BL/6 background) were subjected to high fat diet for sixteen weeks. Weight, cholesterol, HDL, and LDL levels, endothelial function (isometric tension recording), oxidative stress (NADPH oxidase expression, dihydroethidium fluorescence) and inflammatory parameters (inducible nitric oxide synthase, interleukin-6 expression) were assessed. CD40L expression, weight, leptin and lipids were increased, and endothelial dysfunction, oxidative stress and inflammation were more pronounced in wild type mice on a high fat diet, all of which was almost normalized by CD40L deficiency. Similar results were obtained in diabetic db/db mice with CD40/TRAF6 inhibitor (6877002) therapy. In a small human study higher serum sCD40L levels and an inflammatory phenotype were detected in the blood and Aorta ascendens of obese patients (body mass index > 35) that underwent by-pass surgery. Conclusion: CD40L controls obesity-associated vascular inflammation, oxidative stress and endothelial dysfunction in mice and potentially humans. Thus, CD40L represents a therapeutic target in lipid metabolic disorders which is a leading cause in cardiovascular disease.